Instructional Strategies in Teaching Engineering at a Distance: Faculty perspective - Ariadurai, S. Anbahan; Manohanthan, Rajalingam (International Review of Research in Open and Distributed Learning, 2008)
This paper presents research on a convenience sample of the Open University of Sri Lanka’s engineering faculty. Examined in this research are faculty’s opinions on the instructional strategies they use to teach engineering courses at a distance. First, this paper details the pedagogical strategies used by the faculty, which is then followed by an overview of faculty’s opinions on the strengths and weaknesses of engineering courses offered by the Open University of Sri Lanka. Recommendations are given to improve the overall effectiveness of the engineering courses. It is anticipated the adoption of these recommendations will result in greater student competency and lower drop-out rates.